2017
DOI: 10.1016/j.jclepro.2017.08.208
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating lean thinking and life cycle assessment to reduce environmental impacts of plastic injection moulded products

Abstract: a b s t r a c tIn the last decades, environmental footprint of the product manufacture has emerged as an important public concern, causing manufacturers to re-assess their product's environmental impacts. Responding to global outcry on global warming, world leaders have agreed to limit global temperature rise to less than 2 C above the temperature in pre-industrial times. As a result, governments and industrial leaders around the world have proposed a roadmap for 80% emissions reduction by 2050. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 41 publications
0
34
0
2
Order By: Relevance
“…In a past study, TPM was shown to be among ten lean tools that simultaneously help with productivity and environmental efficiency [4]. Reduced defect rate, decreased number of machine failures, and alleviated time inefficiencies were achieved by TPM implementation in a past study [222]. The contribution of TPM to environmental performance due to increased machine life, reduced hazardous leakage, and emissions is also evident in the literature [138,165,169].…”
Section: Tools and Methods Constructmentioning
confidence: 96%
See 2 more Smart Citations
“…In a past study, TPM was shown to be among ten lean tools that simultaneously help with productivity and environmental efficiency [4]. Reduced defect rate, decreased number of machine failures, and alleviated time inefficiencies were achieved by TPM implementation in a past study [222]. The contribution of TPM to environmental performance due to increased machine life, reduced hazardous leakage, and emissions is also evident in the literature [138,165,169].…”
Section: Tools and Methods Constructmentioning
confidence: 96%
“…However, it does not have any practical tools to measure sustainable performance. That is, the underlying reason of its integration with other methodologies such as lean, LCA, six-sigma, and TQM [137,219,[221][222][223][224]. Many lean tools were used to derive sustainability solutions at both intraand inter-organizational levels [169,225,226].…”
Section: Tools and Methods Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…Input and output data across the system boundaries were collected, validated and normalized. Examples of studies deploying LCA in manufacturing include Cheung et al [49]; Zhang and Haapala [50]; Thammaraksa et al [51], among others.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…Durante las últimas décadas, la huella ambiental de la fabricación de productos se ha convertido en una Herramienta preocupación de carácter público, lo que hace que las empresas revalúen los impactos ambientales de la fabricación [26]. En el trabajo de [27] se propone un modelo integrador entre LM y producción más limpia (PML) denominado LCPC (Lean CleanerProduction Benchmarking), este busca la evaluación de la producción más limpia en empresas de diferentes tamaños.…”
Section: Fig 3 Estudios Por Sectorunclassified